The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.3390/rs1040842
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Soil Line Influence on Two-Band Vegetation Indices and Vegetation Isolines

Abstract: This paper introduces derivations of soil line influences on two-band vegetation indices (VIs) and vegetation isolines in the red and near infra-red reflectance space. Soil line variations are described as changes in the soil line parameters (slope and offset) and the red reflectance of the soil surface. A general form of a VI model equation written as a ratio of two linear functions (e.g., NDVI and SAVI) was assumed. It was found that relative VI variations can be approximated by a linear combination of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…The first trend indicates that the variations of the VIs show a similar trend to the soil line parameters. This motivated us to derive and quantify the variations of VIs in terms of the soil line parameters in our previous work [1]. There are clear trends that govern the effects of soil line variations on the VIs, which are the focus of our analyses in the next section.…”
Section: Variations Of Vismentioning
confidence: 99%
See 4 more Smart Citations
“…The first trend indicates that the variations of the VIs show a similar trend to the soil line parameters. This motivated us to derive and quantify the variations of VIs in terms of the soil line parameters in our previous work [1]. There are clear trends that govern the effects of soil line variations on the VIs, which are the focus of our analyses in the next section.…”
Section: Variations Of Vismentioning
confidence: 99%
“…The first objective is to validate the derived expressions [1]. In [1] we have showed that soil line variation influences on VIs almost linearly.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations